NUMERICAL STUDY AND DESIGN OF SIDE-DIFFUSERS FOR FORMULA-SAE CAR - Chatpattanasiri, C.; Bunpapong, K.; Sahastharachai, M.; Puangkird, B. (My University, 2022)
This research focuses on designing side-diffusers for Formula Student race car. The aim is to reduce the lap time in a circular track called Skid-pad event by mean of increasing downforce generated by the diffusers, a ground effect aerodynamic device. Utilizing three-dimensional CFD simulation via cloud computing to obtain the most optimal design among the studied parameters. The study employs SST k-omega turbulence model with an incompressible flow and isothermal assumptions and the CFD model is validated via wind tunnel testing. Finally, the results show that the optimal outlet angle of 32 degrees due to the behavior vortex above the diffuser and the higher the outlet to inlet height, the lesser downforce.
Keywords: CFD; Diffusers; Downforce; Formula Student; Skid-pad; SST k-omega